Notes On the Intergenerational Reflections of the Expansion of Fundamental Rights - Ricken, Guilherme (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
The aim of this article is to outline some intergenerational consequences arising from the expansion of fundamental rights. To do so, it will be exposed, at first, their historic route in the Western world, emphasizing that they emerged as rights of freedom. In the next moment, we will show the effects of the continued expansion of those rights, like the state intervention in the economy and the public debt, and its corollaries, namely, economic cycles, inflation and crises. Finally, we intend to present a liberal theory of the fundamental rights that is adequate to the principle of intergenerational equity, based on Murray Rothbard’s ethic of liberty.